Holothuria (Semperothuria) roseomaculata n. sp. (Aspidochirotida: Holothuriidae), a coral-reef inhabiting sea cucumber from the western Pacific Ocean - Kerr, Alexander M. (Zootaxa, 2013)
Holothuria (Semperothuria) roseomaculata n. sp. is described from the main islands of Yap, Federated States of Micro-nesia. The ossicles are similar to those of its sister species, the sympatric H. (S.) flavomaculata Semper, 1868, but the new species is easily recognised, both in the field and among preserved specimens, by its much larger, rose-coloured dorsal papillae that fade to white in alcohol. Holothuria (S.) roseomaculata n. sp. appears to be an endemic of the tropical west-ernmost Pacific Ocean; it has been recorded from Okinawa to New Caledonia.